EXPANSION OF INFORMATION BASE OF THE STATE STATISTICS FOR IMPORT SUBSTITUTION NEEDS - Irina N Nikulina (Статистика и экономика)
The article give reasons for the state statistics information base expansion to increase the research efficiency of balancing of the import and domestic food ratio in the course of import substitution. To this purpose the author offers to expand the volume of information gathered at the present by the authorities of the state statistics concerning the share of import melons and gourds in the regional food markets as well as its actually realized volume and prospective demand for similar local output.